ChemInform Abstract: Sesquiterpenoids with anti‐MDR Staphylococcus aureus Activities from Ferula ferulioides. Issue 36 (September 2015) - Liu, Tao; Wang, Shuangying; Xu, Lili; Fu, Wei; Gibbons, Simon; Mu, Qing
Abstract All seven newly isolated compounds have been tested against multi‐drug‐ and methicillin‐resistant Staphylococcus aureus strains SA1199B, XU212, ATCC25923, RN4220, EMRSA‐15 and EMRSA‐16.